2007
DOI: 10.1158/0008-5472.can-06-3940
|View full text |Cite
|
Sign up to set email alerts
|

A Cathepsin K Inhibitor Reduces Breast Cancer–Induced Osteolysis and Skeletal Tumor Burden

Abstract: Osteoclasts mediate bone destruction in breast cancer skeletal metastases. Cathepsin K is a proteinase that is secreted by osteoclasts and degrades bone. Here, immunohistochemistry revealed that cathepsin K was expressed not only by osteoclasts but also by breast cancer cells that metastasize to bone. Following intratibial injection with cathepsin Kexpressing human BT474 breast cancer cells, tumor-bearing mice treated with a clinical dosing regimen of cathepsin K inhibitor (CKI; 50 mg/kg, twice daily) had oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(126 citation statements)
references
References 21 publications
4
112
0
5
Order By: Relevance
“…Because of species differences between the binding sites of human versus rodent CatK, there are usually significant reductions in potency against the rodent CatK with the inhibitors developed against the human enzyme. Even if the human osteoporosis dose of AFG-495 has not been determined, it was dosed via intraperitoneal injection twice daily to achieve sufficient high drug exposure in mice (15). Interestingly in that study, AFG-495 at 50 mg/kg, i.p., twice daily for 39 days reduced tumor burden by 62%, whereas a single high bolus subcutaneous injection of ZOL 100 mg/kg did not inhibit skeletal tumor burden (15).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of species differences between the binding sites of human versus rodent CatK, there are usually significant reductions in potency against the rodent CatK with the inhibitors developed against the human enzyme. Even if the human osteoporosis dose of AFG-495 has not been determined, it was dosed via intraperitoneal injection twice daily to achieve sufficient high drug exposure in mice (15). Interestingly in that study, AFG-495 at 50 mg/kg, i.p., twice daily for 39 days reduced tumor burden by 62%, whereas a single high bolus subcutaneous injection of ZOL 100 mg/kg did not inhibit skeletal tumor burden (15).…”
Section: Discussionmentioning
confidence: 99%
“…Even if the human osteoporosis dose of AFG-495 has not been determined, it was dosed via intraperitoneal injection twice daily to achieve sufficient high drug exposure in mice (15). Interestingly in that study, AFG-495 at 50 mg/kg, i.p., twice daily for 39 days reduced tumor burden by 62%, whereas a single high bolus subcutaneous injection of ZOL 100 mg/kg did not inhibit skeletal tumor burden (15). Of note, Le Gall and colleagues also confirmed that AFG-495 did not inhibit subcutaneous growth of breast cancer B02 tumor xenografts in nude mice at a dosing regimen that was demonstrated to inhibit skeletal tumor burden, demonstrating that CatK inhibition does not affect breast cancer cell proliferation (15,24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations